Financial and environmental benefits from fruit trees in Myanmar’s central dry zone: Case Study from Htee Pu Climate Smart Village - Manilay, Alessandro A.; Barbon, Wilson John; Cabriole, Marie Aislinn; Myae, Chan; Thant, Phyu Sin; Gummadi, Sridhar; Monville-Oro, Emilita; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The village of Htee Pu in the Township of Nyaung-U, Mandalay Region suffers from drought, water scarcity, infertile soil, and high ambient temperature being part of Myanmar’s central rry zone area. One of the Climate-Smart Agriculture (CSA) technologies and practices introduced by the International Institute for Rural Reconstruction (IIRR), Climate Change, Agriculture and Food Security (CCAFS) Southeast Asia, International Development Research Center (IDRC) and the Community Development Association in the village was fruit tree-based agroforestry. This study estimated the potential financial and environmental benefits that can be derived from the CSA option. The study revealed that the potential market value of the fruits harvested would amount to USD 1.07 Million from 2021 to 2035 or an average of USD 71,072/year. The production of fruits represents the provisioning ecosystem service of the fruit trees. Per household, the average financial benefit could amount to USD 47,398 over the 15-year period or USD 3,160 per year. In addition, the fruit trees would be able to provide a regulating ecosystem service by being able to potentially sequester 5,682 tCO2 per year with an estimated value of USD 47,725. Fruit production and carbon sequestration have a combined economic value of USD 118,797 per year. There is an upsurge in global interest in ecosystem restoration and the rehabilitation of degraded landscapes. The findings of this study are relevant to environmental agencies working to stabilize the central Dry Zone of Myanmar as including dryland horticulture and small farm agroforestry will benefit not only the local environment but also the people living in the area by making fruits available for their nourishment and livelihood. Development and agricultural agencies, on the other hand, can include CSA as a pathway for addressing degradation on small farms and associated landscapes.